2006
DOI: 10.1038/modpathol.3800695
|View full text |Cite
|
Sign up to set email alerts
|

Gains of COL1A1-PDGFB genomic copies occur in fibrosarcomatous transformation of dermatofibrosarcoma protuberans

Abstract: Dermatofibrosarcoma protuberans is a superficial low-grade sarcoma that rarely evolves into a high-grade fibrosarcoma. Dermatofibrosarcoma protuberans is genetically characterized by the unbalanced chromosomal t(17;22)(q21;q13), usually in the form of a supernumerary ring chromosome. The product of this chromosomal translocation is the chimeric gene COL1A1-PDGFB (collagen type I alpha I-platelet-derived growth factor beta), which is amplified at low levels in the ring chromosome. The aims of this study were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
45
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 24 publications
11
45
1
Order By: Relevance
“…We thus analyzed if the presence of COL1A1/PDGFB extra fusion signals was frequently observed in DFSP-FS. In agreement with Stacchiotti et al (2011), no significant relationship was observed in contrast to previously reported series, including earlier results from our group (Abbott et al, 2006;Macarenco et al, 2008;Segura et al, 2011). The limited number of such cases included in these studies may explain these negative results.…”
Section: Comparison Between Rt-pcr and Fish Techniquescontrasting
confidence: 80%
See 3 more Smart Citations
“…We thus analyzed if the presence of COL1A1/PDGFB extra fusion signals was frequently observed in DFSP-FS. In agreement with Stacchiotti et al (2011), no significant relationship was observed in contrast to previously reported series, including earlier results from our group (Abbott et al, 2006;Macarenco et al, 2008;Segura et al, 2011). The limited number of such cases included in these studies may explain these negative results.…”
Section: Comparison Between Rt-pcr and Fish Techniquescontrasting
confidence: 80%
“…A positive result using DCDF probes requires two fusion signals, an event that is very unlikely to occur by chance. A limited number of studies on DFSP using FISH techniques has been reported and most of them were small series using both PDGFB break-apart (Abbott et al, 2006;Macarenco et al, 2008;Patel et al, 2008) and DCDF COL1A1/PDGFB probes (Craver et al, 2006;Maire et al, 2007;Segura et al, 2011). Regarding PDGFB break-apart probes, the largest series reported included 27 patients and the presence of the translocation was observed in 96% of cases (Patel et al, 2008).…”
Section: Comparison Between Rt-pcr and Fish Techniquesmentioning
confidence: 93%
See 2 more Smart Citations
“…The product of this chromosomal translocation is the fusion gene COL1A1-PDGFB, which has been detected in both GCF and DFSP (Simon et al, 1997). Interestingly, one to three genomic copies of this fusion gene are commonly observed in DFSP (Abbott et al, 2006 In this study, we aimed to determine the frequency and genomic copy number of COL1A1-PDGFB fusion in cases of pure GCF and in distinct areas of hybrid cases of GCF/DFSP to better understand the biology of this histologic evolution. In addition, we aimed to determine the molecular cytogenetic signature of the individual mononuclear and giant cell components of GCF.…”
Section: Introductionmentioning
confidence: 97%